Sense of coherence as a predictor of onset of depression among Japanese workers: a cohort study - Kimura Kazumoto; Wada Keiko; Ishikawa Yumiko; Haruyama Yasuo; Sairenchi Toshimi; Muto Takashi (BMC, 2011)
Abstract Background The ability to predict future onset of depression is required for primary prevention of depression. Many cross-sectional studies have reported a correlation between sense of coherence (SOC) and the presence of depressive symptoms. However, it is unclear whether SOC can predict future onset of depression. Therefore, whether measures to prevent onset of depression are needed in for persons with low SOC is uncertain. Thus, the aim of this cohort study was to determine whether SOC could predict onset of depression and to assess the need for measures to prevent onset of depression for persons with low SOC. Methods A total of 1854 Japanese workers aged 20-70 years in 2005 who completed a sense of coherence (SOC) questionnaire were followed-up until August 2007 using their sick-pay records with medical certificates. Depression was defined as a description of "depression" or "depressive" as a reason for sick leave on the medical certificates. The day of incidence of depression was defined as the first day of the sick leave. Risk ratios of SOC for onset of depression were calculated using a multivariate Cox proportional hazards model. Results Of the 1854 participants, 14 developed depression during a mean of 1.8 years of follow-up. After adjustment for gender and age, the risk ratio of high SOC compared with low SOC for sick leave from depression was 0.18 (95% confidence interval [CI], 0.04 to 0.79). The area under the receiver operating characteristic curve of SOC was 0.70 (95% CI, 0.58 to 0.82). Conclusions The SOC may be able to predict onset of depression in Japanese workers. Measures to prevent onset of depression for persons with low SOC might be required in Japanese workplaces. Thus, SOC could be useful for identifying persons at high risk for future depression.